2020
DOI: 10.3389/fmicb.2020.00765
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Among Divergence Time and Coding and Non-coding Elements in the Shaping of Fungal Mitochondrial Genomes

Abstract: Divergence Time and Mitogenome Shaping and investigated its relationship with coding and non-coding elements as well as with the length of mitogenomes. Altogether, our results demonstrated that introns and HEGs are key elements on mitogenome shaping and its presence on fast-evolving mtDNAs could be mostly explained by its divergence time, although the intron sharing profile suggests the involvement of other mechanisms on the mitochondrial genome evolution, such as horizontal transference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 92 publications
3
32
1
Order By: Relevance
“…These results suggest that the presence or absence of mitochondrial introns cannot serve as a taxonomic marker in themselves, and that care should be taken to remove these highly dynamic sequences from phylogenetic analyses. However, a recent study by Fonseca et al (2020) estimated that there may be a correlation between the divergence time of each Hypocrealean fungal species they investigated and the quantity of coding and noncoding elements in the mtDNA, in addition to the effect these elements have on the length of mitochondrial genomes between species. They showed that introns and HEGs are key components on mitochondrial genomes in that the presence of these elements indicates more rapidly evolving mtDNA, which could be partially explained by species divergence time, despite that the intron pattern shared between species suggests the involvement of other mechanisms of evolution, such as horizontal transference.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results suggest that the presence or absence of mitochondrial introns cannot serve as a taxonomic marker in themselves, and that care should be taken to remove these highly dynamic sequences from phylogenetic analyses. However, a recent study by Fonseca et al (2020) estimated that there may be a correlation between the divergence time of each Hypocrealean fungal species they investigated and the quantity of coding and noncoding elements in the mtDNA, in addition to the effect these elements have on the length of mitochondrial genomes between species. They showed that introns and HEGs are key components on mitochondrial genomes in that the presence of these elements indicates more rapidly evolving mtDNA, which could be partially explained by species divergence time, despite that the intron pattern shared between species suggests the involvement of other mechanisms of evolution, such as horizontal transference.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the presence or absence of mitochondrial introns cannot serve as a taxonomic marker in themselves, and that care should be taken to remove these highly dynamic sequences from phylogenetic analyses. However, a recent study by Fonseca et al (2020) estimated that there may be a correlation between the divergence time of each Hypocrealean fungal species they investigated and the quantity of coding and noncoding elements in the GLARE ET AL. mtDNA, in addition to the effect these elements have on the length of mitochondrial genomes between species.…”
Section: Annotation and Comparative Mitochondrial Genomicsmentioning
confidence: 99%
See 3 more Smart Citations